Strictinin: A Key Ingredient of Tea - Tzen, Jason T. C. (Molecules (Basel, Switzerland), 2023)
Strictinin is a relatively tiny ellagitannin, which is found in many plants as a minor constituent. Catechins are known as the major constituents in the young leaves of most tea plants, while strictinin was found as a major constituent in the Pu’er tea plant. In some Pu’er tea varieties, strictinin was identified as the most abundant phenolic compound rather than catechins. In the past decade, strictinin was demonstrated to possess several functional activities, including antiviral, antibacterial, anti-obesity, laxative, anticaries, anti-allergic, antipsoriatic, antihyperuricemia, antidiabetic, and anticancer effects. These functional activities were in accordance with the therapeutic effects empirically perceived for Pu’er tea. Evidently, strictinin is the key ingredient in Pu’er tea that acts as a herbal medicine. In functionally-based applications, an instant powder of Pu’er tea infusion was formulated as an active raw material to be supplemented in food, cosmetics, and beverages; a new type of tea named Bitter Citrus Tzen Tea was developed by combining three teas empirically consumed to expel the cold, and new edible oral care products were designed for caries prevention by supplementation with Pu’er tea extract. More functional activities and practical applications of strictinin are scientifically anticipated in follow-up research.